A Prospective Study of the Effect and Safety of Atorvastatin on the Recurrence of Chronic Subdural Hematoma after Burr Hole Surgery - Bumpetch, Duangkamol; Sitthinamsuwan, Bunpot; Nunta-aree, Sarun (Asian Journal of Neurosurgery, 2023)
Introduction Chronic subdural hematoma (CSDH) is a common neurosurgical condition. Recent studies showed efficacy of atorvastatin in reducing the requirement of surgical treatment. This study aimed to evaluate the efficacy and safety of atorvastatin in reducing the recurrence of CSDH after burr hole surgery.Methods This prospective study included patients with CSDH who underwent burr hole surgery. Atorvastatin at 20 mg per day was administered to all patients for 4 weeks postoperatively. The major outcome was the recurrence rate of CSDH at 8 weeks following the operation.Results Seventy-three patients who completed the 4-week course of atorvastatin were included. The mean age was 73.9 years. The most common cause of CSDH was falling. The mean hematoma volume was 106.3 mL. There was no adverse effect of atorvastatin in all of 73 patients. During the 8-week postoperative period, recurrent CSDH was found in 2 of 73 (2.7%) patients. In a comparison of the recurrence rate of CSDH between patients with use of atorvastatin from the present and previous studies (2.6–4.8%), and patients without use of atorvastatin from previous studies (9.8–19%), a marked reduction in recurrent CSDH after burr hole surgery was found in patients with use of atorvastatin.Conclusion An administration of atorvastatin of 20 mg daily for 4 weeks following burr hole surgery is safe and may be helpful in reducing the recurrence rate of CSDH after burr hole surgery.
Keywords: atorvastatin; burr hole; chronic subdural hematoma; recurrence